2017
DOI: 10.1186/s12871-017-0411-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined spinal-epidural anesthesia for cesarean delivery in a patient with cor triloculare biventriculare

Abstract: BackgroundCor triloculare biventriculare accounts for approximately 0.31% of cases of congenital heart disease (CHD). Moreover, people with cor triloculare biventriculare always have shorter life spans, and cases of gestation are rare. There have been various related reports of cor triloculare biventriculare in recent years.Case presentationWe described an emergency cesarean section of a 30-year-old, 38-weeks-pregnant woman suffering from cardiac insufficiency and fetal distress. Combined spinal-epidural anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A number of case reports have demonstrated acceptable cardiovascular stability with low dose CSE in pregnancies with higher cardiac risk in the last decade even in cases of cyanotic tetralogy of Fallot and Eisenmenger syndrome (13)(14)(15)(16) . Han et al (17) reported a case in which CSE was safely administered to a term mother suffering from congenital heart disease (cor triloculare biventriculare) and fetal distress. A baby boy was delivered without any complication to the mother or fetus.…”
Section: Discussionmentioning
confidence: 99%
“…A number of case reports have demonstrated acceptable cardiovascular stability with low dose CSE in pregnancies with higher cardiac risk in the last decade even in cases of cyanotic tetralogy of Fallot and Eisenmenger syndrome (13)(14)(15)(16) . Han et al (17) reported a case in which CSE was safely administered to a term mother suffering from congenital heart disease (cor triloculare biventriculare) and fetal distress. A baby boy was delivered without any complication to the mother or fetus.…”
Section: Discussionmentioning
confidence: 99%
“…A sudden decrease in preload and afterload due to spinal single shot is a condition that aggravates the patient's condition, so in some literature this technique is contraindicated to use in patient with heart disease. 9 Administration of fluids and drugs as prophylaxis to prevent hypotension or bradycardia due to regional anesthesia can be a new problem for patients with low cardiovascular reserves.…”
Section: Discussionmentioning
confidence: 99%